2020
DOI: 10.4103/jehp.jehp_291_20
|View full text |Cite
|
Sign up to set email alerts
|

The association between nurses' moral distress and sleep quality and their influencing factor in private and public hospitals in Iran

Abstract: BACKGROUND: Nurses in their workplace, for a variety of reasons, always face moral distress that is an underlying issue in the nursing profession, which can lead to problems such as reduced quality and quantity of care and sleep disorder. Besides, given the increased privatization of hospitals, this study aimed to explore the association between nurses' moral distress and sleep quality and its comparison among nurses in private and public hospitals. MATERIALS AND METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Physical manifestations of moral distress among RNs were reported in studies from Iran (Fard et al, 2020), Canada (Forozeiya et al, 2019), Norway (Jansen et al, 2020), USA (Prestia et al, 2017;Sauerland et al, 2014;Wilson et al, 2013;Wolf et al, 2016) and Uganda (Harrowing & Mill, 2010). Symptoms experienced included fatigue (Harrowing & Mill, 2010;Wolf et al, 2016), insomnia (Fard et al, 2020;Forozeiya et al, 2019;Jansen et al, 2020;Wilson et al, 2013;Wolf et al, 2016), hypertension (Jansen et al, 2020;Wolf et al, 2016) and appetite loss (Wolf et al, 2016). Moral residue, the enduring, cumulative effect of morally distressing situations (Stovall et al, 2020), manifested in insomnia, cardiovascular, gastrointestinal and menstrual problems (Pavlish et al, 2016), alopecia (Sauerland et al, 2014) and activated exacerbations of physical and psychological illnesses (Pavlish et al, 2016).…”
Section: 'I'm Totally Overwhelmed': the Effects Of Moral Distress On ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Physical manifestations of moral distress among RNs were reported in studies from Iran (Fard et al, 2020), Canada (Forozeiya et al, 2019), Norway (Jansen et al, 2020), USA (Prestia et al, 2017;Sauerland et al, 2014;Wilson et al, 2013;Wolf et al, 2016) and Uganda (Harrowing & Mill, 2010). Symptoms experienced included fatigue (Harrowing & Mill, 2010;Wolf et al, 2016), insomnia (Fard et al, 2020;Forozeiya et al, 2019;Jansen et al, 2020;Wilson et al, 2013;Wolf et al, 2016), hypertension (Jansen et al, 2020;Wolf et al, 2016) and appetite loss (Wolf et al, 2016). Moral residue, the enduring, cumulative effect of morally distressing situations (Stovall et al, 2020), manifested in insomnia, cardiovascular, gastrointestinal and menstrual problems (Pavlish et al, 2016), alopecia (Sauerland et al, 2014) and activated exacerbations of physical and psychological illnesses (Pavlish et al, 2016).…”
Section: 'I'm Totally Overwhelmed': the Effects Of Moral Distress On ...mentioning
confidence: 99%
“…Physical manifestations of moral distress among RNs were reported in studies from Iran (Fard et al, 2020), Canada (Forozeiya et al, 2019), Norway (Jansen et al, 2020), USA (Prestia et al, 2017;Sauerland et al, 2014;Wilson et al, 2013;Wolf et al, 2016) and Uganda (Harrowing & Mill, 2010). Symptoms experienced included fatigue (Harrowing & Mill, 2010;Wolf et al, 2016), insomnia (Fard et al, 2020;Forozeiya et al, 2019;Jansen et al, 2020;Wilson et al, 2013;Wolf et al, 2016), hypertension (Jansen et al, 2020;Wolf et al, 2016) and appetite loss (Wolf et al, 2016).…”
Section: 'I'm Totally Overwhelmed': the Effects Of Moral Distress On ...mentioning
confidence: 99%
“…The ability to coping can be affected and destroyed by exposure to many stressors, and in a vicious cycle, it can lead to other negative consequences. Accordingly, and given the complications caused by moral distress in the performance of EMS technicians and the fact that the level of exposure of ICU nurses and EMS technicians to moral distress has been reported to be high [18][19][20], and also to the best of our knowledge, no study was found to investigate moral distress in EMS technicians, this study was conducted to investigate the relationship between moral distress and coping in EMS technicians working in emergency medical service bases affiliated to East Azerbaijan University of Medical Sciences to provide basic information on the level of coping of technicians in these wards, identify one of the possible factors related to coping in them, and reveal the necessity of dealing with solutions to reduce and control moral distress and promote coping in EMS technicians.…”
Section: Introductionmentioning
confidence: 99%